GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Tracking freshwater snail diversity: a historical and environmental study in sub-tropical South Africa - Martin H. Le Roux; Wynand Malherbe; Luc Brendonck; Nico J. Smit; Lizaan de Necker (Hydrobiologia, 2026)
Freshwater snails are integral to aquatic ecosystems, contributing to nutrient cycling and serving as bioindicators of environmental health. However, this group faces growing threats from human activities, habitat degradation, and invasive species. This study investigated the diversity, distribution, and abundance of freshwater snails in a sub-tropical South African region, comparing current populations with historical data from the 1960s–1980s. The ecological impacts of invasive species on native snails and ecosystem functions were also assessed. Field surveys at multiple sites, employing qualitative and quantitative collection methods, measured snail populations alongside water quality and habitat characteristics. Multivariate analyses, including canonical correspondence analysis (CCA), explored the relationships between environmental variables and snail community composition. Nine freshwater snail taxa were identified, with the invasive Tarebia granifera —absent from historical records—dominating. CCA results showed distinct differences in community composition between sites with and without T. granifera . The presence of this invasive species corresponded with reduced diversity and abundance of native snails, particularly in fast-flowing habitats with limited aquatic vegetation. This research highlights the need for monitoring native and invasive species, highlighting conservation priorities to protect native snails and mitigate the ecological and human health impacts of invasive species.

Evaluating the ecological consequences of Tarebia granifera density on benthic diatom communities in South African river systems - Ruan Gerber; Johannes J. Pearson; Anrich Kock; Wynand Malherbe; Lizaan de Necker (Biological Invasions, 2025)
Invasive species pose a significant threat to global freshwater biodiversity. The invasive snail Tarebia granifera has been reported to exploit microphytobenthos and detritus, potentially exercising a greater feeding impact compared to other invertebrates. Despite its presence in several important conservation regions in the country, little information exists regarding the effects of T. granifera on South African ecosystems. This study investigated the impact of T. granifera on benthic diatom communities in north-eastern South African river systems. Benthic diatoms, T. granifera , and water samples were collected from three ecologically and economically important river systems and it was determined whether changes in benthic diatom diversity and community structures were associated with differences in T. granifera densities. Results indicated distinct diatom community structures between sites with varying T. granifera densities. Higher densities of T. granifera were associated with decreased diatom species diversity, disrupted functional groups, and alterations in species composition and dominance patterns while sites with fewer or no T. granifera exhibited higher diatom diversity, species richness, and a broader range of functional groups. The study findings support the hypothesis that T. granifera negatively impacts benthic diatom communities, emphasising the need for comprehensive management strategies to mitigate the effects of invasive species on aquatic ecosystems.

A stable isotope analysis of the dietary patterns of the aquatic apex predator, the African tigerfish ( Hydrocynus vittatus ) - Ruan Gerber; Lizaan de Necker; Johan H. J. van Vuren; Yoshinori Ikenaka; Shouta M. M. Nakayama; Mayumi Ishizuka; Victor Wepener; Nico J. Smit (Journal of Fish Biology, 2023)
Stable isotope analyses, specifically δ 13 C and δ 15 N, are useful tools increasingly used to understand ecosystem function, food web structures, and consumer diets. Although the iconic tigerfish Hydrocynus vittatus is regarded as an apex predator in southern African freshwater systems, little information is available regarding their feeding behavior and how this may change with growth or differ between ecosystems, with most information stemming from stomach content analyses (SCA). The aim of the present study was to address this lack of information through a baseline study of the diet of large and small tigerfish in various lentic and lotic ecosystems in South Africa using stable isotope methods. Fish and various food web components and food sources were collected from two river and two lake ecosystems in South Africa. The δ 13 C and δ 15 N values for all samples were determined and multivariate analyses and Bayesian analytical techniques applied to determine the feeding ecology of H. vittatus and how this may differ with size and habitat type. Analyses revealed a substantial difference in the type and abundance of food sources contributing to the diet of H. vittatus between ecosystems, most prominently between the lotic systems, where less dietary specialization was observed, and lentic systems where more specialization was observed. Furthermore, there was a distinct difference in diet between small and large tigerfish, especially in the lotic system, indicating an ontogenetic diet shift as tigerfish grow and further supporting previous SCA studies. This is the first study of its kind on the African continent for H. vittatus and the findings illustrate the value of stable isotope analysis in providing in‐depth information into the feeding ecology of consumers and how this may differ between size classes and habitat types.

Temporal dynamics of a subtropical floodplain pool after 2 years of supra-seasonal drought: a mesocosm study - Lizaan de Necker; Ruan Gerber; Johan van Vuren; Victor Wepener; Nico J. Smit; Luc Brendonck (Hydrobiologia, 2022)

Cloning and characterization of major antigenic determinants of human cytomegalovirus Ad169 seen by the human immune system - W. Lindenmaier; Antje Necker; Susanne Krause; Renate Bonewald; J. Collins (Archives of Virology, 1990)